2022
DOI: 10.54063/ojc.2022.v43i03.06
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Currency Futures Issuance on Foreign Exchange Rate Volatility in India

Abstract: This article examines the effect of currency futures on foreign exchange rate volatility in India focusing on USD-INR, EUR-INR, GBP-INR and JPY-INR. For the period from February 2002 to February 2020, the daily exchange rate values of all the four currencies against the Indian rupee (INR) were collected. The Augmented Dicky Fuller (ADF) test of the unit root was performed to check the stationarity of the time series data utilized in the study. After verifying the presence of heteroskedasticity with the ARCH LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
2
2
Order By: Relevance
“…They have not found any strong evidence supporting the destabilizing effect of the FX derivatives market. However, in contrast with the study by Jin et al (2021), Rani et al (2022) and Singh and Patra (2022) show that the unconditional variance of the USD/INR exchange rate decreases in the post period. Rani et al (2022) and Singh and Patra (2022) also investigated GBP, EUR, and JPY futures traded on the National Stock Exchange.…”
Section: Literature Reviewcontrasting
confidence: 87%
See 2 more Smart Citations
“…They have not found any strong evidence supporting the destabilizing effect of the FX derivatives market. However, in contrast with the study by Jin et al (2021), Rani et al (2022) and Singh and Patra (2022) show that the unconditional variance of the USD/INR exchange rate decreases in the post period. Rani et al (2022) and Singh and Patra (2022) also investigated GBP, EUR, and JPY futures traded on the National Stock Exchange.…”
Section: Literature Reviewcontrasting
confidence: 87%
“…However, in contrast with the study by Jin et al (2021), Rani et al (2022) and Singh and Patra (2022) show that the unconditional variance of the USD/INR exchange rate decreases in the post period. Rani et al (2022) and Singh and Patra (2022) also investigated GBP, EUR, and JPY futures traded on the National Stock Exchange. They came to the same conclusion that the unconditional variance in the GBP/INR exchange rate decreases in the post period.…”
Section: Literature Reviewcontrasting
confidence: 87%
See 1 more Smart Citation
“…As a whole, the study concluded that exports are predominantly influenced by factors other than real exchange rate volatility. Rani et al (2022) observed the influence of currency futures on volatility of Indian rupee exchange rate based on Indian rupee vis-a-vis US dollar, Euro, UK pound and Japanese yen covering a period from February 2002 to February 2020. The results of GARCH (1,1) model brings out that volatility persists for considered bilateral currency's exchange rates.…”
Section: Literature Reviewmentioning
confidence: 99%